Two-dimensional optimization problem of plant location - Linh, Tran Gia; Vinh, Phan Ngoc (Vietnam Journal of Mechanics, 2001)
In this paper, the following matters are presented: the adjoint problem of the two-dimensional matter propagation problem; the algorithm for determination of a domain in which a plant can be located so that the values of the pollution-level reflecting functional does not exceed a given value at considered sensitive areas; application of this algorithm for numerical experiments to a typical problem